Visible or Invisible? Korean High School Studentsâ Current Schooling Experiences in the United States - Bogum Yoon; Claudia Haag (Arizona State University, 2010)
This qualitative study examined the current schooling experiences of eight Korean high school students in the United States. By comparing and contrasting recent immigrant adolescents and 1.5/2nd generation students, the purpose of this study was to explore how their identities as Koreans or Korean Americans were formed and shifted while they engaged with American teachers and peers in mainstream contexts. The findings suggest that even in the same ethnic group, differences were conspicuous. The newcomer group desperately wished to assimilate to mainstream culture by associating with American classmates. On the other hand, the 1.5/2nd generation group lived bi-culturally with dual identities as Korean and American and shifted their identities according to their convenience. Despite these differences, both of the groups suffered a similar experience by receiving unwelcome gestures from their mainstream teachers and peers: the newcomers as invisible outsiders and the 1.5/2nd generation as visible and marked outsiders.